Relationship between Iron Metabolism and Thyroid Hormone Profile in Patients with Hyperthyroidism - Monica Verma; Renuka Verma; Kiran Dahiya; Isha Malik; Vasudha Dhupper; Ashuma Sachdeva (Recent Developments in Medicine and Medical Research Vol. 14, 2021)
Background: Hyperthyroidism denotes to hyperfunctioning of thyroid gland. It is generally accompanied by alterations in erythropoiesis. The precise mechanism remains unclear. Study Objectives: The present study was conducted to know the association of thyroid disorders and abnormalities in hematological parameters. Conclusion: Alterations in thyroid status produces changes in serum ferritin and has an impact on other hematologic parameters too. Thyroid hormones directly influence iron metabolism by affecting ferritin levels. Although, on one hand raised free iron levels are toxic for body and acts as marker of oxidative stress, on the other side hyperferritinemiaplays a protective role against this increased oxidative stress seen in hyperthyroidism.